1983
DOI: 10.1159/000260695
|View full text |Cite
|
Sign up to set email alerts
|

Highly Acid SnF2and TiF4Solutions

Abstract: In a previous in vitro study, a considerable fluoride uptake was found in scaled root surfaces following treatment with a TiF4 solution (1.1 M F, pH 1.0). In spite of the low pH of the solution, no demineralization could be detected in the root tissue. This led to speculation that certain cations, known to act as complexers, might inhibit such demineralization. In the present experiment a SnF2 solution (1.6 MF, pH 1,0) resulted in an even greater deposition of F in scaled root surfaces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Enamel treated with the TiF 4 solution showed an etched appearance which is consistent with the small profilometric loss after treatment observed both in this study ( table 1 ) and also by Magalhães et al [2008]. This contrasts with the layer produced by treatment with the TiF 4 varnish, which probably provides a mechanical and chemical barrier, even though it has cracks [Tveit et al, 1983;Büyükyilmaz et al, 1997;Hove et al, 2006;Vieira et al, 2006]. Besides the layer on the enamel surface, TiF 4 -varnish-treated enamel had a higher surface concentration of both Ti and F than the TiF 4 -solution-treated surface.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Enamel treated with the TiF 4 solution showed an etched appearance which is consistent with the small profilometric loss after treatment observed both in this study ( table 1 ) and also by Magalhães et al [2008]. This contrasts with the layer produced by treatment with the TiF 4 varnish, which probably provides a mechanical and chemical barrier, even though it has cracks [Tveit et al, 1983;Büyükyilmaz et al, 1997;Hove et al, 2006;Vieira et al, 2006]. Besides the layer on the enamel surface, TiF 4 -varnish-treated enamel had a higher surface concentration of both Ti and F than the TiF 4 -solution-treated surface.…”
Section: Discussionsupporting
confidence: 89%
“…Most studies focusing on the preventive effect of fluoride on erosion used fluoride compounds which have been applied over years in caries prevention, such as NaF, AmF, SnF 2 or acidulated phosphate fluoride. More recently, other agents, such as titanium tetrafluoride (TiF 4 ), have been investigated for erosion prevention [Tveit et al, 1983;Büyükyilmaz et al, 1997;van Rijkom et al, 2003;Vieira et al, 2005Vieira et al, , 2006Hove et al, 2006Hove et al, , 2007Schlueter et al, 2007;Magalhães et al, 2008].…”
Section: Buzalafmentioning
confidence: 99%
“…According to the literature, the beneficial action of TiF 4 solution on dental erosion has been attributed to its low pH (around 1.2), favoring the linking between titanium and oxygen of the group phosphate, thus leading to the formation of a titanium dioxide glaze-like layer on the surface. 18,21,22 It is probable that in the present study this protective layer have been rapidly removed due to the high erosive challenge, thus not allowing the observation of such a protective effect.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, other agents such as titanium tetrafluoride (TiF 4 ) have been investigated for erosion prevention. [18][19][20][21][22][23][24][25] In respect to TiF 4 solution, in vitro studies have shown its inhibitory effect on erosion. 18,19,22,23 However, other studies have shown the opposite.…”
Section: Resultsmentioning
confidence: 99%
“…This might enhance the depth of penetration of fluoride ions and promote the formation of CaF 2 . The titanium ions might play an important role as they might substitute calcium in the apatite lattice and show a strong tendency to complex with phosphate groups, forming stable titanium dioxide layer [14][15][16] . Moreover, it is suggested that titanium interacts with organic components of the enamel surface, leading to an increased fluoride uptake by enamel.…”
Section: Discussionmentioning
confidence: 99%